2006
DOI: 10.1253/circj.70.1226
|View full text |Cite
|
Sign up to set email alerts
|

Displacement of the Beating Heart Induces an Immediate and Sustained Increase in Myocardial Reactive Oxygen Species

Abstract: isplacement of the heart during beating heart surgery can reduce coronary blood flow and cardiac output (CO) 1 and to normalize hemodynamics the Trendelenburg position is often employed with or without fluid and pharmacological intervention. 1 Methods to reestablish coronary flow could be deemed reperfusion therapy and cardiac reperfusion after a brief ischemic insult can increase reactive oxygen species (ROS), 2 which may promote cardiac dysfunction and/or arrhythmias. 3-5 However, no studies have investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…8 The ROS production in the mitochondria contributes to pathological process such as cardiomyopathy, 32 aging, 33 apoptosis, 34 hypoxia, 35 and ischemia/reperfusion. 36,37 The complexes I and III of the mitochondrial electron transport chain (ETC) are regarded as the major sites of ROS production. It has been reported that PKAcat activates the respiratory chain complex I and/or III, and decreases the generation of ROS in isolated mitochondria.…”
Section: Pkacat-induced Ros Generation In Mitochondriamentioning
confidence: 99%
“…8 The ROS production in the mitochondria contributes to pathological process such as cardiomyopathy, 32 aging, 33 apoptosis, 34 hypoxia, 35 and ischemia/reperfusion. 36,37 The complexes I and III of the mitochondrial electron transport chain (ETC) are regarded as the major sites of ROS production. It has been reported that PKAcat activates the respiratory chain complex I and/or III, and decreases the generation of ROS in isolated mitochondria.…”
Section: Pkacat-induced Ros Generation In Mitochondriamentioning
confidence: 99%